Pengembangan Senam Konservasi Universitas Negeri Semarang Tahun 2012 - Setiawan, Ipang; Pujianto, Agus; Setiawan, Arif (Media Ilmu Keolahragaan Indonesia, 2013)
Conservation gymnastic consisting of three a part which is instillation parts, a part fundamental and a part refrigerations. This research constitute research that aims to result product as developmental as Conservation gymnastic. Steps that is utilized in this research utilizes 7 (seven) main stage. ÃÂ Base observational result Ã¢â¬Â college student response, ÃÂ 84 % respondent perceive pleasings, ÃÂ or 14 % respondent answer so-sos, and 2 % respondent answer discontented. Developmental aspect Ã¢â¬Â college student response 79 % respondent perceive to make easy studyings, 19 % respondent answer so-sos, and 2 % respondent answer to get into a mess studyings. Aspect processes learning Ã¢â¬Â college student response 83 % respondent perceive are easily, 15 % respondent answer so-sos, and 2 % respondent answer distresses. Expectation aspect Ã¢â¬Â college student response 86 % respondent answer Can be kept on, ÃÂ reason makes easy learning, 2 % respondent answer Can be kept on, ÃÂ reason up to havenÃ¢â¬â¢t available the other gymnastic, ÃÂ and 2 % respondent answer donÃ¢â¬â¢t be kept on, reason gets into a mess studying, and 0 % or no respondent. ÃÂ Simpulan pengembangan is conservation gymnastic can help to increase lecturer earthly concern fitness, employee, college student and society. ÃÂ  Gymnastic stirred development conservation and conservation gymnastic music, ÃÂ was updated is assessed apropos and truth, ÃÂ progressively simple its power, progressively lucid, ÃÂ its music gets menggungah spirit, ÃÂ can do by whoever.